Pengaruh terapi aktivitas kelompok terhadap penurunan gejala depresi lansia di panti usia lanjut Ais’yah Surakarta - Vitri Dyah Herawati; Indriyati Indriyati; Widiyono Widiyono (Holistik Jurnal Kesehatan, 2021)
Effectiveness of cognitive behavioral group therapy for depression in elderly people living in institutions.Background: Depression in the elderly caused many factors. The impact of depression decreases the quality of life of the elderly. Nursing interventions need to deal with depression problems in the elderly. Group activity therapy, perceptions stimulation of low self-esteem, and cognitive-behavioral therapy recommend for depression elderly with low self-esteem.Purpose: Knowing the effectiveness of cognitive-behavioral group therapy for depression in elderly people living in institutions.Method: The research design is a quasi-experiment with a pre-post test with a control group, with 30 participants divided by 2 groups (each group comprises 15 participants). The instrument using Geriatric Depression Scale (GDS) and analyzed using the Independent T-TestResults: Finding a significant decrease in depression in the elderly with low self-esteem in the two groups with a decrease of 67.4% in the intervention group and 31.9% in the control group (p-value <0.05), and there was a significant relationship between the characteristics of the elderly (gender, education, marital status, occupation, and comorbid physical illness) with depression in the elderly with low self-esteem (p-value <0.05).Conclusion: Cognitive-behavioral group therapy for depression is recommended to decrease depression in the elderly with low self-esteem.Keywords: Cognitive behavioral group therapy; Depression; Elderly people; Living in institutions.Pendahuluan: Depresi pada orang tua dapat disebabkan oleh berbagai faktor. Dampak depresi sangat membuat kualitas hidup lansia menurun. Diperlukan intervensi keperawatan untuk menangani masalah depresi pada lansia. Terapi aktivitas kelompok, stimulasi persepsi harga diri rendah dan terapi kognitif perilaku direkomendasikan untuk depresi pada lansia harga diri rendah.Tujuan : Mengetahui  Pengaruh terapi aktivitas kelompok terhadap penurunan gejala depresi lansiaMetode : Desain penelitian menggunakan quasi experiment with pre post test, dengan sampel berjumlah  30 partisiapan yang dibagi menjadi 2 kelompok masing-masing 15 partisipan (kelompok intervensi dan kelompok kontrol). Alat pengumpul yang digunakan Geriatric Depression Scale (GDS). Data dianalisis menggunakan uji Independen T-Test.  Hasil : Menunjukkan ada penurunan depresi pada kelompok intervensi sebelum dilakukan TAK (nilai pre-test) adalah 10,89,setelah dilakukan TAK mengalami peningkatan nilai rerata yaitu menjadi 15,93. Kelompok kontrol dalam penelitian ini juga mengalami peningkatan penerapan TAK yaitu dari nilai 10,30 menjadi 10,52. dan ada hubungan bermakna antara karakteristik lansia (jenis kelamin, pendidikan, status perkawinan, pekerjaan dan penyakit fisik penyerta) dengan depresi pada lansia harga diri rendah (p value < 0,05).Simpulan: TAK stimulasi persepsi harga diri rendah dan terapi kognitif perilaku direkomendasikan untuk depresi pada lansia harga diri rendah.